Low-voltage current-mode preamplifier based Latch comparator - Jankatkit, Thongchai; Kasemsuwan, Varakorn (My University, 2016)
This paper presents a low-voltage latch current comparator. The circuit was designed on the basis of current mirror, preamplifier and latch circuits and also various circuit techniques; quasi-floating gate to reduce the input impedance, bulk driven technique for the circuit to be operable under low supply voltage and positive feedback to increase the gain and the overall speed. From the simulation results, which were presented with 0.18 um CMOS technology, the circuit can operate well at the supply voltage of 0.5 volt and the resulting propagation delay time were 2.2 nS and 1.4 nS when the input current differences are 1 uA and 10 uA, respectively. The total power dissipation was 79 uW.
Keywords: current comparator; dynamic latch comparator; low voltage